Endocytic Adaptors in Cardiovascular Disease - Cui, Kui; Dong, Yunzhou; Wang, Beibei; Cowan, Douglas B.; Chan, Siu-Lung; Shyy, John; Chen, Hong (Frontiers in Cell and Developmental Biology, 2020)
Endocytosis is the process of actively transporting materials into a cell by membrane engulfment. Traditionally, endocytosis was divided into three forms: phagocytosis (cell eating), pinocytosis (cell drinking), and the more selective receptor-mediated endocytosis (clathrin-mediated endocytosis); however, other important endocytic pathways (e.g. caveolin-dependent endocytosis) contribute to the uptake of extracellular substances. In each, the plasma membrane changes shape to allow the ingestion and internalization of materials, resulting in the formation of an intracellular vesicle. While receptor-mediated endocytosis remains the best understood pathway, mammalian cells utilize each form of endocytosis to respond to their environment. Receptor-mediated endocytosis permits the internalization of cell surface receptors and their ligands through a complex membrane invagination process that is facilitated by clathrin and adaptor proteins. Internalized vesicles containing these receptor-ligand cargoes fuse with early endosomes, which can then be recycled back to the plasma membrane, delivered to other cellular compartments, or destined for degradation by fusing with lysosomes. These intracellular fates are largely determined by the interaction of specific cargoes with adaptor proteins such as the epsins, disabled-homolog 2 (Dab2), the stonin proteins, epidermal growth factor receptor substrate 15, and adaptor protein 2 (AP-2). In this review, we focus on the role of epsins and Dab2 in controlling these sorting processes in the context of cardiovascular disease. In particular, we will focus on the function of epsins and Dab2 in inflammation, cholesterol metabolism, and their fundamental contribution to atherogenicity.